Constructive description of monogenic functions in a harmonic algebra of the third rank - Plaksa, S. A.; Shpakovskii, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
By using analytic functions of a complex variable, we give a constructive description of monogenic functions that take values in a commutative harmonic algebra of the third rank over the field of complex numbers. We establish an isomorphism between algebras of monogenic functions in the case of transition from one harmonic basis to another.